Механизмы культурной диффузии - Шостак, С. (Социология: теория, методы, маркетинг, 2005)
The article is dedicated to the sociological conceptualization of the cultural diffusion process. Sources of conceptualization of this phenomenon, its constituents and typological models were analyzed by the author. Special attention has been paid to the cultural diffusion mechanism in modern society. The following mechanisms were defined in the article: migration, tourism, trade, leisure, and mass media, which represent relocation diffusion and expansion diffusion.